OC-080 Excess Steroid Use in IBD: Too Much, How Much and Why? Results From A Nationwide Audit. (17th August 2016) - Raine, T; Bassi, A; Fogden, E; Hayee, B; Limdi, JK; Ludlow, H; McLaughlin, S; Parkes, GC; Patel, P; Smith, MA; Selinger, C
Abstract : Introduction: Corticosteroids are the cornerstone of inducing remission in IBD but are limited in their ability to maintain remission, and associated with significant side effects. This is the first nationwide outpatient study of steroid use in IBD and factors affecting their use. Methods: We audited consecutive IBD patients attending clinics at 11 centres over 3 months using a web-based assessment tool. Cases meeting criteria for steroid excess (SE) as defined by ECCO guidelines were blind peer reviewed and classified as non-IBD use, unavoidable and inappropriate steroid excess (ISE). Associations between steroid use and patient and institutional factors were analysed. Results: Of 1177 patients [48% CD, 49% UC, 3% IBD-U] 79% were in remission/mild disease, 18.5% had moderate and 2.5% severe disease. In the previous 12 months, 30% had received steroids, 13.8% had SE. Peer review revealed that SE was inappropriate in 51.2% of these (8% non-IBD use; 40.7% unavoidable). Excess steroid exposure was more common in patients with active UC compared to active CD (41.6% vs 26.6%; p = 0.02). In multivariate analysis, disease activity was a significant predictor of SE/ISE. In addition, being established on anti-TNF agents protected against SE and ISE in CD. Exposure to thiopurine (SE + ISE) and starting anti-TNF therapy (ISE) were associated with excess steroid use in UC. CD patients from centres with an IBD MDT were less likely to have SE, similarly CD patients in centres with combined surgical clinics were less likely to experience SE and ISE. Care in centres with dedicated IBD clinics was associated with less SE and ISE in patients with UC. Centres with large numbers of GI trainees showed higher rates of SE in UC and SE and ISE in CD. (All of above independent predictors on multi-variate with significance p < 0.001) Conclusion: We identified inappropriate excess steroid use in 7% of UK IBD patients. Risk factors for steroid exposure differed between UC and CD, likely reflecting inter alia, differences in access to biologic drugs. Our study is the first to demonstrate positive effects of service configurations (IBD MDT, dedicated IBD clinics, combined surgical clinics) on treatment outcomes even after correction for differences in disease severity. There was an association between ISE in Crohn's and the number of GI trainees per centre suggesting possible gaps in training. Routine recording of excess steroid exposure is feasible and should be considered as a quality marker for outcomes of IBD services. Disclosure of Interest: None Declared